Flavonoids are indispensable for complete male fertility in rice. (9th May 2020) - Wang, Lanxiang; Lam, Pui Ying; Lui, Andy C W; Zhu, Fu-Yuan; Chen, Mo-Xian; Liu, Hongjia; Zhang, Jianhua; Lo, Clive
Abstract : Complete male fertility in rice requires the presence of flavonoids, and a combination of different classes appears to be essential for pollen tube germination and growth inside pistils. Abstract: Flavonoids are essential for male fertility in some but not all plant species. In rice ( Oryza sativa ), the chalcone synthase mutant oschs1 produces flavonoid-depleted pollen and is male sterile. The mutant pollen grains are viable with normal structure, but they display reduced germination rate and pollen-tube length. Analysis of oschs1 /+ heterozygous lines shows that pollen flavonoid deposition is a paternal effect and fertility is independent of the haploid genotypes ( OsCHS1 or oschs1 ). To understand which classes of flavonoids are involved in male fertility, we conducted detailed analysis of rice mutants for branch-point enzymes of the downstream flavonoid pathways, including flavanone 3-hydroxylase (OsF3H; flavonol pathway entry enzyme), flavone synthase II (CYP93G1; flavone pathway entry enzyme), and flavanone 2-hydroxylase (CYP93G2; flavone C -glycoside pathway entry enzyme). Rice osf3h and cyp93g1 cyp93g2 CRISPR/Cas9 mutants, and cyp93g1 and cyp93g2 T-DNA insertion mutants showed altered flavonoid profiles in anthers, but only the osf3h and cyp93g1 cyp93g2 mutants displayed reduction in seed yield. Our findings indicate that flavonoids are essential for complete male fertility in rice and a combination of different classes (flavanones, flavonols, flavones, and flavone C -glycosides) appears to be important, as opposed to the essential role played primarily by flavonols that has been previously reported in several plant species.